The Feasibility of Harvesting and Extraction of Logging Residues in Sabah - Ahlan, Joseph (1998)
Effective harvesting and utilisation of log and logging residues are important, in achieving the sustainable forest management and to maximize the government revenue, in the light of declining supply of conventional logs. The aim of this study was to evaluate the feasibility of harvesting and extracting the logging residues, to estimate their economic value, to determine quality and quantity of logging residues and types, to derive a volume equations for quantifying logging residues, and to determine the factors affecting their extraction. The type, quality and quantity of logging residues were determined from two different tenures of timber concessions which were categorised into three different operations based on altitudes, vegetation types, topography and terrain characteristics. The "with" and "without" the Project approach was used in determining the Incremental Net Benefit (INB) of harvesting and extracting the logging residues. The economic value of logging residues was determined by applying formulas that express the concept of the stumpage value of timber. The volume equation for logging residues was estimated using the OLS and WLS regression methods following the normal volume equation for log.